An Overview on Fundamental Physical Constants and Primary Physical Parameters - Vladimir S. Netchitailo (New Frontiers in Physical Science Research Vol. 9, 2023)
Every four years, the Committee on Data for Science and Technology (CODATA) publishes a self-consistent set of physics fundamental constants and conversion factors for international usages. As an alternative to the Big Bang Model, the World-Universe Model (WUM) proposed a fundamentally different depiction of the World in 2013. Currently, gravity has a special place in physics as it is the only interaction that cannot be described by a quantum theory. This chapter: 1) Gives the short history of Classical Physics before Special Relativity; 2) Calculates Fundamental Physical Constants based on experimentally measured Rydberg constant, Electrodynamic constant, Electron Charge-to-Mass Ratio, and Planck constant; 3) Discusses Electrodynamic constant and Speed of Light; 4) Considers Dimensionless Fundamental Parameters (Dirac Large Number Q and Dimensionless Rydberg Constant \(α\)); 5) Calculates Newtonian Constant of Gravitation based on the Inter-connectivity of Primary Physical Parameters; 6) Makes a detailed analysis of the Self-consistency of Fundamental Physical Constants and Primary Physical Parameters through the prism of WUM. The results of the analysis point to: 1) Discontinuing using the notion “Vacuum” and its characteristics (Speed of Light in Vacuum, Characteristic Impedance of Vacuum, Vacuum Magnetic Permeability, Vacuum Electric Permittivity); 2) Accepting the exact numerical values of Electrodynamic constant, Planck constant, Elementary charge, and Dimensionless Rydberg Constant \(α\). WUM recommends the predicted value of Newtonian Constant of Gravitation in 2018 to be considered in CODATA Recommend Values of the Fundamental Physical Constants 2022.